VITAMINS FOR DIABETES MELLITUS - Dzhalilov M.U; Asadov Asad Madilloevich (Proximus Journal Publishing, 2025)
Diabetes mellitus is a pathology accompanied by a violation of carbohydrate, fat and protein metabolism, which leads to such consequences as a deficiency of vital vitamins. The development of chronic complications, including diabetic polyneuropathy, retinopathy and cardiovascular diseases, can develop against the background of a lack of water- and fat-soluble vitamins. This article discusses the role of vitamins in the pathogenetic chain of diabetes mellitus and the correction of metabolic disorders in this disease. Based on the analysis of scientific data, it was found that the development of diabetic complications, including neuropathy, angiopathy and dysfunction of the immune system, is also associated with a deficiency of vitamins B, D, C and E. It was found that correction of vitamin status can slow down the progression of complications and improve the quality of life of patients. Particular attention is paid to vitamin B12, the deficiency of which is often found in patients receiving metformin. The data obtained emphasize the need for individual selection of vitamin support in the complex therapy of diabetes mellitus.
Keywords: Diabetes mellitus; vitamin